Review of the Marriage Law on Wahbah Zuhaili's Views on Misyar Marriage - Amania, Malinda Hafizaturrizqo; Gusti Muzainah (Fakultas Syariah UIN Antasari, 2023)
Misyar marriage is a form of marriage in which, in practice, the wife does not receive the rights she should rightfully obtain from her husband, such as financial support and a place to live. Recently, misyar marriages have also occurred in Indonesia. There is a debate about the status and position of misyar marriages, with the majority of scholars considering them prohibited (haram), as the wife is deprived of certain rights. However, Wahbah az-Zuhaili is one scholar who holds a different view on the legality of misyar marriages. In his Fatawa Mu’ashirah, az-Zuhaili expresses his opinion on the permissibility of this type of marriage. This research is a normative legal study, specifically a library research approach. The research nature involves content analysis, and legal materials are collected through document studies. The Marriage Law in Indonesia has several provisions that are inconsistent with the practice of misyar marriages, including the purpose of marriage, marriage registration, rights and obligations of spouses, marriage agreements, and the requirements for husbands wishing to practice polygamy. In broad terms, the implementation of misyar marriages, when examined in various aspects within the Indonesian Marriage Law, is not in accordance. The author disagrees with Wahbah az-Zuhaili's view regarding the permissibility of such marriages. The author believes that this type of marriage tends to bring more harm than benefit. The government should actively participate in monitoring through authorized marriage institutions, and if possible, marriages of this nature should be prohibited in Indonesia.